Association between total cholesterol and all-cause mortality in oldest old: a national longitudinal study - Hu, Fan; Wang, Zhiqiang; Liu, Yujie; Gao, Ying; Liu, Shangbin; Xu, Chen; Wang, Ying; Cai, Yong (Frontiers in Endocrinology, 2024)
A common sense is that lower serum cholesterol levels are better. However, a growing number of researches have questioned this especially for the oldest old. The current study was to assess the association between total cholesterol and all-cause mortality in a group of people aged 85 years old and over.We selected 903 Chinese old participants who aged ≥85 years from the Chinese Longitudinal Healthy Longevity Survey(CLHLS) at baseline in 2012. The participants were followed up until death or until December 31, 2014. The outcome was all-cause mortality.The univariate and multivariate cox regression analyses were used to estimate risk levels of all-cause mortality. We stratified the participants into three groups (<3.40, 3.40-4.39, ≥4.39 mmol/L) based on the restricted cubic splines methods. The survival probability according to total cholesterol category was calculated using the Kaplan-Meier curves, and the log-rank test was performed to analyze differences between the groups.During the follow-up of three years, 282 participants died, 497 survived and 124 lost to follow-up. There was significant relationship between the total cholesterol and lower risk of all-cause mortality in the multivariable Cox regression analysis (HR=0.88, 95% CI: 0.78-1.00). Based on the restricted cubic splines methods, the total cholesterol was converted from a continuous variable to a categorical variable. The populations were divided into three groups (<3.40, 3.40-4.39, ≥4.39 mmol/L) according to the total cholesterol categorized by cutoff values. Compared to the total cholesterol level of <3.40 mmol/L, populations in the total cholesterol level of 3.40-4.39 mmol/L (HR = 0.72, 95% CI: 0.53-0.97) and ≥4.39 mmol/L (HR =0.71, 95% CI: 0.52-0.96) groups had lower all-cause mortality in multivariate cox regression analysis and higher survival probability in survival analysis. When two groups were divided, similar results were found among the populations in the total cholesterol level of ≥3.40 mmol/L compared to the populations in the total cholesterol level of <3.40 mmol/L groups.In oldest old aged 85 and older, serum total cholesterol levels are inversely associated with all-cause mortality. This study suggested that total cholesterol should be maintained to acceptable levels ( ≥ 3.40 mmol/L) in oldest old to achieve longevity.